What WAS Hot (and Not) in Literacy: What We Can Learn. Issue 1 (24th August 2013) - Cassidy, Jack; Ortlieb, Evan
Abstract: The annual What's Hot, What's Not in Literacy Survey has helped to define the literacy agenda and highlight topics receiving attention in the field over the last 15 years. The ebb and flow of the field of literacy often shifts with changes in legislation, policy, and curricula. As a result, what was formerly hot may subsequently receive less attention or even fall off the list entirely. Some topics that were once on the list never received the attention that some educators believed they deserved. This article examines the background behind previously hot issues and other topics that were on the list but never considered hot. Abstract : FREE author podcast